2022
DOI: 10.1002/gj.4450
|View full text |Cite
|
Sign up to set email alerts
|

Microfacies and depositional environment of Tarbur Formation (Upper Cretaceous‐Lower Palaeocene) Zagros area, southwestern Iran

Abstract: Over 3,000 m of Upper Cretaceous‐Lower Palaeocene sediments belonging to the Tarbur Formation were studied in seven stratigraphic sections around Shiraz city (south Zagros Basin, SW of Iran). The Tarbur Formation is divided into two informal lithostratigraphic units: a lower well‐bedded rudist limestone and an upper massive rudist limestone. Both units comprise rudist particles as a major organo‐detrital component. Microscopic studies have identified the presence of the following carbonate microfacies types in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Studies by Afghah (2016, 2022), Afghah and Yousefzadeh (2006), Abyat et al (2007), Vaziri‐Moghaddam et al (2005) in Fars (South Zagros) have shown that the formation of reefs in the Tarbur Formation had more ideal conditions and spread wildly. There were true reefs that were deposited in the back reefs lagoons of the Sachun Evaporation Formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Afghah (2016, 2022), Afghah and Yousefzadeh (2006), Abyat et al (2007), Vaziri‐Moghaddam et al (2005) in Fars (South Zagros) have shown that the formation of reefs in the Tarbur Formation had more ideal conditions and spread wildly. There were true reefs that were deposited in the back reefs lagoons of the Sachun Evaporation Formation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Afghah (2016Afghah ( , 2022, Afghah and Yousefzadeh (2006), Abyat et al (2007), Vaziri-Moghaddam et al (2005)…”
Section: Distal Outer Rampmentioning
confidence: 99%
“…Faujas-Saint-Fond, 1798-1803Goldfuss, 1826Goldfuss, -1844Milne Edwards & Haime, 1857;Nötling, 1897;Trauth, 1911;Dietrich, 1917;Umbgrove, 1925;Wells, 1933Wells, , 1934Alloiteau, 1936Alloiteau, , 1952bAlloiteau, , 1958Kuzmicheva, 1985Kuzmicheva, , 1987Tchéchmédjiéva, 1986Tchéchmédjiéva, , 1995Filkorn, 1994;Leloux, 1999Leloux, , 2004Baron-Szabo, 2000, 2006, 2008Filkorn et al, 2005;Jell et al, 2011;Löser, 2012;Baron-Szabo et al, 2023) as well as in analyses primarily dealing with Maastrichtian stratigraphy and sedimentology (e.g. Gill et al, 1966;Sohl & Koch, 1984;Görmüş et al, 2019;Afghah, 2022). Frequently, corals have been documented from rudist-dominated limestones (e.g.…”
Section: Introductionmentioning
confidence: 99%